Chemical Fractionation Of Cu And Zn And Their Impacts On Microbial Properties In Slightly Contaminated Soils - Aiju, Liu; Honghai, Wang; Peiling, Gao; Hong-zhi, Xu (International Journal of Agricultural Research, Innovation and Technology, 2013)
Chemical fractionation of Cu and Zn in bulk soil and its effects on soil microbial properties were determined in Cu and Zn contaminated soils (Cu: 35.57~46.37 mg·kg-1, Zn: 74.33~127.20 mg·kg-1) sampled from an agricultural field in outskirts of Zibo, China during the month of September, 2011. A sequential extraction technique (SET) was used for metals chemical fractionation analysis in soils and a correlation analysis was applied to determinate the effects of metal on soil microbial properties. Chemical speciation showed that Cu and Zn were mostly present in the residual fraction and their concentrations in the most labile fraction (acid soluble fraction) were the lowest in the investigated soils. However, the correlation analysis indicated that the labile forms of Cu/Zn, such as its acid soluble, reducible or oxidizable fractions, were usually significantly negatively correlated with the tested microbial activities at 0.05 or 0.01 probability levels. These results indicate that the metal labile fractions could exert an inhibitory effect on the soil microbial parameters even in the minor contaminated soils. Int. J. Agril. Res. Innov. & Tech. 3 (1): 20-25, June, 2013 DOI: http://dx.doi.org/10.3329/ijarit.v3i1.16045